Stochastic mechanism of broadening spectral density of synchrotron radiation of relativistic electron - Mazmanishvili, A.S. (Вопросы атомной науки и техники, 2021)
The consideration is based on the study of the spectral profile of the synchrotron radiation (SR) line of a relativistic electron orbiting in a circular orbit in the uniform magnetic field. Fast stochastic fluctuations accompanying the motion of the electron during emission of SR quanta lead to the formation of spectral contour of each SR harmonic and it’s broadening. It is shown that the joint broadening of the set of harmonics causes broadening of the SR spectrum as the whole. The results of numerical calculations on the formation of the final SR spectral density of a relativistic electron are presented. In order to obtain precision characteristics, the formation of SR density in the frequency range exceeding the critical frequency has been studied. Розгляд спирається на вивчення спектрального контуру лінії синхротронного випромінювання (СВ) релятивістського електрона, що обертається по круговій орбіті в однорідному магнітному полі. Швидкі стохастичні флуктуації, які супроводжують рух електрона при емісії квантів СВ, призводять до формування спектрального контуру кожної з гармонік СВ і його розширенню. Показано, що спільне розширення сукупності гармонік обумовлює розширення спектра СВ у цілому. Представлені результати чисельних розрахунків по формуванню підсумкової спектральної щільності СВ релятивістського електрона. З метою отримання прецизійних характеристик вивчено формування щільності СВ в області частот, що перевищують критичну частоту. Рассмотрение опирается на изучение формирования спектрального контура линии синхротронного излучения (СИ) релятивистского электрона, вращающегося по круговой орбите в однородном магнитном поле. Быстрые стохастические флуктуации, сопровождающие движение электрона при эмиссии квантов СИ, приводят к формированию спектрального контура каждой из гармоник СИ и его уширению. Показано, что совместное уширение совокупности гармоник обуславливает уширение спектра СИ в целом. Представлены результаты численных расчетов по формированию итоговой спектральной плотности СИ релятивистского электрона. С целью получения прецизионных характеристик изучено формирование плотности СИ в области частот, превышающих критическую частоту.